2012
DOI: 10.1002/mop.26793
|View full text |Cite
|
Sign up to set email alerts
|

Hexagonal ferrite‐piezoelectric composites for dual magnetic and electric field tunable 8–25 GHz microstripline resonators and phase shifters

Abstract: Microwave magnetoelectric (ME) effects over 8–25 GHz have been studied in bilayers of single crystal Y‐type hexagonal ferrite Ba2Zn2Fe12O22 and polycrystalline lead zirconate titanate (PZT) or single crystal lead magnesium niobate–lead titanate (PMN–PT). The bilayers are made by epoxy bonding or eutecting bonding the ferrite and piezoelectric. The strength of ME interactions A has been measured from data on electric field E tuning of magnetic modes in the ferrite. The electric field produces a mechanical defor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 19 publications
0
8
0
1
Order By: Relevance
“…Tatarenko et al [131] reported the converse ME effect over the [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] GHz range in bilayers of single crystal ZnY and polycrystalline PZT or single crystal PMN-PT. The resonator was tuned by 120 MHz with E = 12 kV/cm, and corresponding ME coupling strength A was about 10 MHz cm/kOe.…”
Section: Resonatorsmentioning
confidence: 99%
“…Tatarenko et al [131] reported the converse ME effect over the [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] GHz range in bilayers of single crystal ZnY and polycrystalline PZT or single crystal PMN-PT. The resonator was tuned by 120 MHz with E = 12 kV/cm, and corresponding ME coupling strength A was about 10 MHz cm/kOe.…”
Section: Resonatorsmentioning
confidence: 99%
“…This requires the creation of novel materials and functionalities, while integrating into non‐volatile electronic devices 8–12. Multiferroic heterostructures,13, 7, 14–24 exhibiting strong strain‐mediated magnetoelectric (ME) coupling between distinct ferromagnetic and ferroelectric phases, have shown great promise for frequency agile microwave applications 25, 1, 3–4, 26–29. In these materials, a single control parameter of voltage‐induced piezo‐strain, arising from ferroelectrics, is used to in situ introduce an effective magnetic anisotropy26, 30–37 and subsequent FMR frequency shift, in elastically‐coupled ferromagnetic phases via the magnetoelastic effect 6, 33, 38–42.…”
mentioning
confidence: 99%
“…Therefore, devices based upon such materials are, in principle, light‐weight, fast, and energy efficient, therefore overcoming some of the intrinsic limitations in conventional microwave components in addition to providing new functionality. In most prototype ME microwave devices such as tunable filters,43 resonators,39 and phase shifters,29 tuning of FMR frequency has been achieved through the use of a linear piezo response, whereby the strain is directly proportional to the applied voltage, without electric polarization switching 44. Upon removing the electric field, the FMR decays to the initial state 27, 44.…”
mentioning
confidence: 99%
“…当电场由-3 kV/cm 增加到 6 kV/cm 时, 可在 [24,58~61] . 这些器件是利用 铁氧体中静磁自旋波(MSW)的传递来工作的 [62,63] , [24,36,64] . Tatarenko 等 人 [24] 构建了 YIG/PZT 磁电可调移相器, 利用电压调 图 6 (网络版彩色)基于多铁异质结的移相器 [24] (a) 磁电微波移相器的原理图, 其由 YIG/PZT 磁电谐振器和微带传感器组成; (b) 施加电场 E= 0 和 7.5 kV/cm 时, 相位角随频率的变化 关系, 插图显示了相位移随电场的变化关系…”
Section: 因此 在磁性薄膜中由电场和磁电耦合产生的等效unclassified